Distribución espacio-temporal de variables fisicoquímicas y biológicas en el hábitat del tiburón ballena Rhincodon typus (Orectolobiformes: Rhincodontidae) al norte del Caribe Mexicano - Cárdenas-Palomo, Natalí; Herrera-Silveira, Jorge; Reyes, Óscar (Revista de Biología Tropical, 2010)
Large groups of whale sharks (Rhincodon typus) are common in the North Mexican Caribbean and gather between May and September each year. We describe their spatial and temporal distribution, and the physicochemical (temperature, dissolved oxygen, light extinction coefficient and salinity) and biological conditions during the presence and absence seasons of R. typus. A total of 26 sampling stations were monitored to record whale shark sightings and physicochemical variables during 10 field campaigns from April 2005 to March 2006. At each station, zooplank-ton and water samples, for chlorophyll-a and nutrients determination, were collected. Physicochemical condi-tions were significantly different between presence-absence seasons (ANOSIM, Rglobal = 0.632). The R. typus season was characterized by low salinity values, and higher temperature, chlorophyll-a, dissolved oxygen and inorganic nitrogen concentrations values. Average zooplankton biomass was lower during the absence season, while recorded the maximum values during the presence one. Furthermore, these values were also observed in areas with higher species abundances, supporting the hypothesis that the site is used by R. typus primarily as a foraging area. We conclude that physicochemical conditions of the study area promote the biological productiv-ity, which explains the spatial and temporal variability of R. typus.